2015
DOI: 10.1111/eip.12250
|View full text |Cite
|
Sign up to set email alerts
|

Understanding access and use of technology among youth with first‐episode psychosis to inform the development of technology‐enabled therapeutic interventions

Abstract: These data will be useful for developing Web-based psychoeducation tools and cognitive remediation video games for youth with FEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
3
42
3
1
Order By: Relevance
“…The second reason could be related to the fact that the study was carried out in 2012 and the pattern of use of digital technology is constantly changing by adapting to the needs of the population. Unlike other previously published studies, a greater use of game console in men was not observed [18].…”
Section: Comparison With Prior Workcontrasting
confidence: 81%
See 2 more Smart Citations
“…The second reason could be related to the fact that the study was carried out in 2012 and the pattern of use of digital technology is constantly changing by adapting to the needs of the population. Unlike other previously published studies, a greater use of game console in men was not observed [18].…”
Section: Comparison With Prior Workcontrasting
confidence: 81%
“…In addition, in a previous survey of access and use of technological tools carried out in 2012 in Montreal on 71 patients with first psychotic episode [18], a greater use of computer (fixed or portable) was reported in comparison to mobile phone or smartphone, reaching 96% vs 70% of frequency (defined as "from daily use up to 2-3 times per week"). This difference in computer preference in front of smartphone could be related to two circumstances.…”
Section: Comparison With Prior Workmentioning
confidence: 97%
See 1 more Smart Citation
“…A survey found that adults with psychotic disorders were as likely as adults without mental illness to form social connections online despite having fewer offline relationships, lower income, and less Internet access (20). Youths with psychotic disorders are particularly amenable to using social media to seek information, support, and treatment (21,22). For example, one study found that 99% of youths with psychosis spent roughly three hours online per day on social media (23).…”
mentioning
confidence: 99%
“…C'est une introduction tout à fait justifiée et c'est d'autant plus pertinent que cela devient l'un des modes de communication privilégiés des nouvelles générations, y compris chez les jeunes psychotiques (Abdel-Baki et al, 2015). L'exploration dans ce domaine est infinie et déroutante comme celle de savoir si un psychiatre peut être « un ami » sur Facebook (Pereira, 2014).…”
unclassified